2024
DOI: 10.1088/1361-6560/ad164d
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a new high-TOF-resolution all-digital brain PET system

Lei Fang,
Bo Zhang,
Bingxuan Li
et al.

Abstract: Objective: Time-of-flight (TOF) capability and high sensitivity are essential for brain-dedicated Positron Emission Tomography (PET) imaging, as they improve the contrast and the signal-to-noise ratio (SNR) enabling a precise localization of functional mechanisms in the different brain regions. 
Approach: We present a new brain PET system with transverse and axial field-of-view (FOV) of 320 mm and 255 mm, respectively. The system head is an array of 6 x 6 detection elements, each consisting of a 3.9 x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To evaluate the effectiveness of DP-RI-Tikhonov in a pseudo-real scenario, we collected four high-quality [ 18 F]FDG brain PET images from a high resolution all-digital brain PET system (Fang et al 2024) as simulation phantoms, as shown in figures 1(f) and 7(f). For simplicity and ease of reading, a simulation phantom is used to analyze the effectiveness of DP-RI-Tikhonov in detail and the remaining three simulation phantoms are used to evaluate the generalization ability of DP-RI-Tikhonov.…”
Section: Application To Simulation Data (1) Experimental Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the effectiveness of DP-RI-Tikhonov in a pseudo-real scenario, we collected four high-quality [ 18 F]FDG brain PET images from a high resolution all-digital brain PET system (Fang et al 2024) as simulation phantoms, as shown in figures 1(f) and 7(f). For simplicity and ease of reading, a simulation phantom is used to analyze the effectiveness of DP-RI-Tikhonov in detail and the remaining three simulation phantoms are used to evaluate the generalization ability of DP-RI-Tikhonov.…”
Section: Application To Simulation Data (1) Experimental Settingmentioning
confidence: 99%
“…(2) Evaluation metrics: Due to the lack of the ground truth PET image x, contrast-to-noise ratio (CNR), CNR = (µ s − µ b ) /σ b , is adopted as the evaluation metric, where µ s and µ b are the mean of signal region and background region respectively, σ b is the standard deviation of background region. In general, the signal region and background region are manually drawn in a region with high activity distribution and a region with relatively uniform activity distribution, respectively (Jomaa et al 2018, Li et al 2023, Fang et al 2024. For better analysis, we calculate the CNR of the brain and the body separately.…”
Section: Application To Real Data (1) Experimental Settingmentioning
confidence: 99%
See 1 more Smart Citation